PEMANFAATAN MULTIMEDIA INTERAKTIF DALAM APLIKASI MOBILE UNTUK PENGENALAN CAGAR BUDAYA PEMALANG - DIDI PURNOMO; Aprilia, Ari Maulidia; Turmudi, Ahmad (JURNAL ILMIAH FAKULTAS TEKNIK, 2025)
he lack of public awareness—especially among younger generations—regarding the importance of cultural heritage preservation presents a major challenge in the digital era. This study aims to develop and evaluate the effectiveness of an educational mobile application based on interactive multimedia to introduce cultural heritage in Pemalang Regency. The application, "Garda Cagar Budaya," was developed using a hybrid approach (HTML, CSS, JavaScript within the Android framework) and applied the ADDIE development model. A quasi-experimental method was used with pretest and posttest involving 10 vocational school students. Results showed a significant improvement in cultural understanding after using the app, with an average normalized gain of 0.483. Additionally, users responded positively to the app's visuals, appeal, and ease of use. This study demonstrates that interactive multimedia in mobile applications can serve as both an effective educational tool and a means of preserving local culture in a technology-adaptive way.